Epidemiology and Seasonality of Endemic Human Coronaviruses in South African and Zambian Children: A Case-Control Pneumonia Study - Baillie, Vicky L.; Moore, David P.; Mathunjwa, Azwifarwi; Park, Daniel E.; Thea, Donald M.; Kwenda, Geoffrey; Mwananyanda, Lawrence; Madhi, Shabir A. (Viruses, 2021)
Endemic human coronaviruses (HCoV) are capable of causing a range of diseases from the common cold to pneumonia. We evaluated the epidemiology and seasonality of endemic HCoVs in children hospitalized with clinical pneumonia and among community controls living in countries with a high HIV burden, namely South Africa and Zambia, between August 2011 to October 2013. Nasopharyngeal/oropharyngeal swabs were collected from all cases and controls and tested for endemic HCoV species and 12 other respiratory viruses using a multiplex real-time PCR assay. We found that the likelihood of detecting endemic HCoV species was higher among asymptomatic controls than cases (11% vs. 7.2%; 95% CI: 1.2–2.0). This was however only observed among children > 6 months and was mainly driven by the Betacoronavirus endemic species (HCoV-OC43 and –HKU1). Endemic HCoV species were detected through the year; however, in Zambia, the endemic Betacoronavirus species tended to peak during the winter months (May–August). There was no association between HIV status and endemic HCoV detection.